Drinking Water Quality of Water Refill Station in Gebang Raya Tanggerang - Veza Azteria; Ernalinda Rosya (Universitas Airlangga, 2023)
Introduction: As a drinking water provider, refill drinking water station must comply with hygiene and sanitation standards for water quality, including the microbiological value standard for clean water. This study was conducted to determine the microbial levels in refill drinking water station and analyze the drinking water quality based on sanitation hygiene observations. Methods: The study included laboratory test methods, cross-sectional analysis tests, and a descriptive analysis. Drinking water sampling and sanitation observations were performed using the total sampling technique on 17 water station. As much as 100 ml of drinking water samples were taken directly from the faucet to refill water with a sterile bottle container. Sanitary hygiene was studied through interviews using an observation sheet. Results and Discussion: The most bacteria were found at 108 per 100ml in Escherichia coli parameters and 866 per 100ml in coliform parameters in the station water samples with the Station 8 (SK) code. The interviews showed that seven station did not meet the criteria for good sanitation hygiene. Conclusion: Sanitary hygiene is carried out to reduce or eliminate bacterial contamination in drinking water. Observations and laboratory tests show that good sanitation is related to drinking water quality.